Meniscal Transplantation - Verdonk, René; Espregueira Mendes, João; Monllau, Joan Carles (Springer Berlin Heidelberg : Imprint: Springer, 2013)
As knowledge of the biomechanical and physiological function of the knee has advanced, meniscal transplantation has become an accepted treatment approach in defined categories of patient with knee pain. In particular, it is an attractive option in the younger patient with incapacitating pain who has previously undergone a total meniscectomy and has an adequately aligned lower limb. When appropriately performed, meniscal transplantation can reduce pain, slow cartilage degeneration, and improve biomechanics.   In this book, acknowledged experts in the field discuss all aspects of meniscal transplantation, covering the use of both allografts and meniscal substitutes, including collagen and polyurethane implants. The relevant basic science is reviewed, indications are explained, and surgical techniques are clearly described, with presentation of the results achieved to date. All the material is up to date, with information on new implants, new techniques, and new surgical approaches. Future trends in the treatment of meniscal lesions are also discussed as we move towards the application of regenerative strategies to restore meniscus function.